Evaluating Mirror Therapy Protocols in Phantom Limb Pain Clinical Trials: A Scoping Review - Limakatso K; McGowan E; Ortiz-Catalan M (Journal of Pain Research)
Katleho Limakatso,1 Eithne McGowan,2 Max Ortiz-Catalan3,4 1Pain Management Unit, Department of Anaesthesia and Perioperative Medicine, Neuroscience Institute, University of Cape Town, Cape Town, South Africa; 2Department of Advanced Reconstruction of Extremities, Sahlgrenska University Hospital, Gothenburg, Sweden; 3Prometei Pain Rehabilitation Center, Vinnytsia, Ukraine; 4Center for Complex Endoprosthetics, Osseointegration, and Bionics, Kyiv, UkraineCorrespondence: Max Ortiz-Catalan, Prometei Pain Rehabilitation Center, Kniaziv Koriatovychiv St. 149, Vinnytsia, 21000, Ukraine, Email maxortizc@outlook.comAbstract: Mirror therapy is among the most widely used treatments for phantom limb pain. However, discrepancies exist in the way it is conducted, and its effectiveness varies widely. The aim of this scoping review was to evaluate the application of mirror therapy across the literature and to identify treatment features unique to studies with clinically significant pain reduction outcomes. Articles published until July 2024 were identified through a systematic search of the following electronic databases: Medline (via EBSCOhost), PubMed, Cochrane Central Register of Controlled Trials, Physiotherapy Evidence Database, PsycINFO (via EBSCOhost), Cumulative Index to Nursing and Allied Health Literature (via EBSCOhost), Africa-Wide Information (via EBSCOhost), and Scopus. Two reviewers independently conducted the screening of titles and abstracts, review of full-text articles, and data extraction. The results were analyzed descriptively. We included 32 studies in this review, 21 of which were deemed effective for achieving clinically significant pain reduction of 50% or 2 points on a 0– 10 scale. There were inconsistencies in various treatment components including treatment setting, type of pre-treatment education, treatment technique, method of exercise delivery, treatment duration, and frequency of treatment sessions. Despite identifying common treatment features across studies with clinically significant pain reduction outcomes, we found no evidence of unanimous consensus in the literature towards any specific protocol for mirror therapy. Establishing a standardized treatment protocol could enhance the reliability and reproducibility of treatment outcomes in future studies and ensure a meaningful comparison between mirror therapy and other treatments in clinical trials and meta-analyses.Keywords: amputation, phantom limb pain, mirror therapy, rehabilitation